IgE Reactivity of Blue Swimmer Crab (Portunus pelagicus) Tropomyosin, Por p 1, and Other Allergens; Cross-Reactivity with Black Tiger Prawn and Effects of Heating - Abramovitch, Jodie B.; Kamath, Sandip; Varese, Nirupama; Zubrinich, Celia; Lopata, Andreas L.; O'Hehir, Robyn E.; Rolland, Jennifer M. (PloS one, 2013)
Shellfish allergy is a major cause of food-induced anaphylaxis, but the allergens are not well characterized. This study examined the effects of heating on blue swimmer crab (Portunus pelagicus) allergens in comparison with those of black tiger prawn (Penaeus monodon) by testing reactivity with shellfish-allergic subjects' serum IgE. Cooked extracts of both species showed markedly increased IgE reactivity by ELISA and immunoblotting, and clinical relevance of IgE reactivity was confirmed by basophil activation tests. Inhibition IgE ELISA and immunoblotting demonstrated cross-reactivity between the crab and prawn extracts, predominantly due to tropomyosin, but crab-specific IgE-reactivity was also observed. The major blue swimmer crab allergen tropomyosin, Por p 1, was cloned and sequenced, showing strong homology with tropomyosin of other crustacean species but also sequence variation within known and predicted linear IgE epitopes. These findings will advance more reliable diagnosis and management of potentially severe food allergy due to crustaceans.